ICE arrests, 2015–2026: Variation in targeting, method, and geography - Chloe N. East; Caitlin Patler; Elizabeth Cox (Proceedings of the National Academy of Sciences, 2026)
We analyze and decompose administrative data on all 1.6 million US Immigration and Customs Enforcement (ICE) arrests from October 2015 to March 2026. Our results reveal that the reality of immigration enforcement diverges sharply from the public narrative that ICE arrests are necessary to protect public safety by removing people who commit crimes: Although arrests spiked at the outset of both Trump presidencies, the share of arrested individuals with criminal convictions fell significantly, with especially marked declines in 2025. A shift in ICE tactics partly explains this pattern, but even conditional on tactic, the share with a criminal conviction declined as arrests rose. Moreover, we find substantial geographic heterogeneity in ICE methods, despite nearly universal declines in the criminal conviction rate. Our findings provide important evidence for policymakers, the general public, and researchers studying this period of immigration policy.